2020
DOI: 10.1002/cpdd.857
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Dissolution and In Vivo Bioequivalence Evaluation of Two Metformin Extended‐Release Tablets

Abstract: The objective of the present study was to evaluate the bioequivalence between generic and branded metformin extended‐release (ER) tablets in Chinese subjects. We tested bioequivalence in vitro and in vivo using a comparative dissolution study and a comparative pharmacokinetic trial. Safety assessments were conducted throughout the entire trial period. The dissolution profiles of the generic formulation expressed obvious extended‐release properties, similar to those of the branded formulation (f2 > 60.0%). Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The drugs in this clinical trial were well tolerated, with GI symptoms and laboratory abnormalities being the primary AEs, most of which did not require special treatment apart from clinical observation until the patient recovered naturally. All AEs were consistent with those listed in the summary of Glucophage ® XR characteristics and other clinical trials [ 15 , 30 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The drugs in this clinical trial were well tolerated, with GI symptoms and laboratory abnormalities being the primary AEs, most of which did not require special treatment apart from clinical observation until the patient recovered naturally. All AEs were consistent with those listed in the summary of Glucophage ® XR characteristics and other clinical trials [ 15 , 30 ].…”
Section: Discussionsupporting
confidence: 74%
“…Recently, Zhou, et al [ 30 ] studied the bioequivalence of two matrix-type metformin extended-release tablets under postprandial conditions. The reference preparation was Glucophage ® XR.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [ 19 ] studied the bioequivalence of MH-SR tablets and Glucophage ® -XR (500 mg) as a reference preparation under fed states. HPLC-MS/MS was used for testing, and 19 blood sampling points within 0–36 h were selected.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, subjects were fed a high-fat diet, as in the present study, and the 90%CI was within 80%-125% based on C max , AUC from time 0 to 36 hours, and AUC 0-∞ . 19 It has been reported that showing bioequivalence of extended-release formulations can be challenging given the complex nature of the in vivo absorption processes. 20,21 However, the present findings were consistent with a previous bioequivalence study of extended-release metformin formulations, 7 further validating the current results.…”
Section: Discussionmentioning
confidence: 99%